F(-2)=0.5(2-(-2))

Simple and best practice solution for F(-2)=0.5(2-(-2)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(-2)=0.5(2-(-2)) equation:


Simplifying
F(-2) = 0.5(2 + -1(-2))

Reorder the terms for easier multiplication:
-2F = 0.5(2 + -1(-2))

Multiply -1 * -2
-2F = 0.5(2 + 2)

Combine like terms: 2 + 2 = 4
-2F = 0.5(4)

Multiply 0.5 * 4
-2F = 2

Solving
-2F = 2

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Divide each side by '-2'.
F = -1

Simplifying
F = -1

See similar equations:

| -2+j= | | 3/y-8=5 | | 4xsquared+2c-1=0 | | 8x(3-2x)(4-x)=0 | | 3x-5/5-2x | | 9x-1=12x-8 | | 1-10x=80 | | 0.01t^2-0.5t+18=0 | | x/-3.1=4.5 | | (3y)^1/3 | | 5x^2-7x+20=0 | | 12(1.5)+4= | | 3x^2-18x+17=0 | | .0725x=10 | | x-26/3=-57/6 | | 3*x=5000 | | R=SQRT(1.3) | | 50/80=x/180 | | 10-3.2(2)= | | 7-.6(x-15)=.1(x-15) | | =200(1+R)2 | | (4x+20)+(2x+60)= | | 7-.6(-22.9-15)=.1(-22.9-15) | | 9+4(-3)= | | 4g+12=18g | | 5+10+3-2-7+1=6x-4x+7x-8x | | 2(-2m+8)+3m-1=90 | | 4+0=9x | | x+8x-3x+10=-16 | | x+9+5x=33 | | x+9+5x=23 | | x^2*x^7*x^7= |

Equations solver categories